Exploring electroactive microenvironments in polymer-based nanocomposites to sensitize bacterial cells to low-dose embedded silver nanoparticles - Moreira, Joana (2022)
The search for alternative antimicrobial strategies capable of avoiding resistance mechanisms in bacteria are highly needed due to the alarming emergence of antimicrobial resistance. The application of physical stimuli as a mean of sensitizing bacteria for the action of antimicrobials on otherwise resistant bacteria or by allowing the action of low quantity of antimicrobials may be seen as a breakthrough for such purpose. This work proposes the development of antibacterial nanocomposites using the synergy between the electrically active microenvironments, created by a piezoelectric polymer (poly(vinylidene fluoride-co-trifluoroethylene) (PVDF-TrFE)), with green-synthesized silver nanoparticles (AgNPs). The electrical microenvironment is generated via mechanical stimulation of piezoelectric PVDF-TrFE/AgNPs films using a lab-made mechanical bioreactor. The generated material's electrical response further translates to bacterial cells, namely Escherichia coli and Staphylococcus epidermidis which in combination with AgNPs and the specific morphological features of the material induce important antibacterial and antibiofilm activity. Both porous and non-porous PVDF composites have shown antibacterial characteristics when stimulated at a mechanical frequency of 4 Hz being the effect boosted when AgNPs were incorporated in the nanocomposite, reducing in more than 80% the S. epidermidis bacterial growth in planktonic and biofilm form. The electroactive environments sensitize the bacteria allowing the action of a low dose of AgNPs (1.69% (w/w)). Importantly, the material did not compromise the viability of mammalian cells, thus being considered biocompatible. The piezoelectric stimulation of PVDF-based polymeric films may represent a breakthrough in the development of antibacterial coatings for devices used at hospital setting, taking advantage on the use of mechanical stimuli (pressure/touch) to exert antibacterial and antibiofilm activity.